Successful Treatment With Omalizumab in a Child With Asthma and Urticaria: A Clinical Case Report - Sirufo, Maria Maddalena; Ginaldi, Lia; De Martinis, Massimo (Frontiers in Pediatrics, 2019)
Childhood urticaria is not rare, although its persistence is less frequent. In children, chronic spontaneous urticaria (CSU) is associated with comorbidities, including asthma, allergic rhinitis, or atopic dermatitis, and many children with CSU have a family history of atopy. The therapeutic approach to CSU in children is the same one recommended by international guidelines for treatment of chronic urticaria in adults. In the European Union, according to the European Medicine Agency, omalizumab is the add-on drug of choice for the management of CSU in adult and adolescent patients (from 12 years of age) with inadequate response to H1 antihistamine therapy. In addition, in children (6 to <12 years of age), it is the add-on therapy of choice to improve asthma control. The management of children with urticaria under 12 is a therapeutic area with few certainties, where omalizumab can be administered only “off-label.”